Imminent Extinction of Australian Myrtaceae by Fungal Disease. (July 2020) - Fensham, Roderick J.; Carnegie, Angus J.; Laffineur, Boris; Makinson, Robert O.; Pegg, Geoff S.; Wills, Jarrah
Abstract : Myrtle rust is a fungal disease that has spread rapidly across the globe, arriving in Australia in 2010. The tree species Rhodomyrtus psidioides is nearly extinct in the wild as a result of the disease, leading to potential disruption of ecosystem function. Many other Myrtaceae may also be threatened and unprecedented impacts of the disease are predicted.